Review on Sensors and Components Used in Robotic Surgery: Recent Advances and New Challenges - Sharad Dinesh; Umesh Kumar Sahu; Dameshwari Sahu; Santanu Kumar Dash; Umesh Kumar Yadav (IEEE Access, 2023)
Surgical robots have been used for many years in the field of medical sciences and engineering. With sophisticated technology governing the world in recent years, surgical robots have benefited from the addition of sensors, actuators, and intelligent control systems, allowing them to function at high precision along with more efficiency. The focus of this study is to present a brief review of sensors and components utilized in robotic surgery that have been studied in recent literature. In the present study, initially, a brief history of robotic surgery is presented, followed by a review on sensors and components in robotic surgery that can be informative for engineers or researchers while designing surgical robots for specific applications. Consequently, highlights of recent trends in the technological advancements in surgical robots have been presented. Further, the paper concludes with recent advances and new challenges in the development of surgical robots.